2015
DOI: 10.3923/ja.2015.272.278
|View full text |Cite
|
Sign up to set email alerts
|

Graphical Determination of Leaf Area Index and its Relationship with Growth and Yield Parameters of Sorghum (Sorghum bicolor L. Moench) as Affected by Fertilizer Application

Abstract: A B S T R A C T Studies were conducted during the 2013 and 2014 cropping seasons at the University for Development Studies, Nyankpala, Ghana to determine leaf area indices of three Sorghum (Sorghum bicolor (L.) Moench) varieties using the graphical approach. Three varieties viz., Kapala, Kadaga and Dorado were planted and applied with three rates: 0-0-0, 45-30-30, 35-20-20 and 45:30:30 of N, P and K, respectively. Treatment combinations were replicated three times in RCBD. Results indicated that the applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…Several approaches; mainly indirect and direct methods of LA measurement have been developed (Blanco & Folegatti, 2003). Although the former method; indirect estimation, has been recommended for monitoring LAI through time and across large spatial areas (Jonckheere et al, 2004), there is however the disadvantage of it being expensive and mostly non-existence in most developing countries (Addai & Alimiyawo, 2015). Consequently, direct methods of estimating LAI have been widely adopted because of the unaffordability and difficulty in assessing leaf area instruments (Dugje & Odo, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches; mainly indirect and direct methods of LA measurement have been developed (Blanco & Folegatti, 2003). Although the former method; indirect estimation, has been recommended for monitoring LAI through time and across large spatial areas (Jonckheere et al, 2004), there is however the disadvantage of it being expensive and mostly non-existence in most developing countries (Addai & Alimiyawo, 2015). Consequently, direct methods of estimating LAI have been widely adopted because of the unaffordability and difficulty in assessing leaf area instruments (Dugje & Odo, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These were corroborated by earlier work of Bavec et al (2007), who reported that variety had influence on leaf area index (LAI) of winter wheat. Addai and Alimiyawo (2015) also reported the influence of variety on LAI in Sorghum (Sorghum bicolor L. Moench). The control (unmulch) had the lowest plant height followed by groundnut (live mulch).…”
Section: Discussionmentioning
confidence: 99%
“…LAI is a dimensionless quantity that characterizes an ecosystem canopy [54]. According to Addai and Alimiyawo [55], a higher LAI value would indicate greater photosynthetic activity that results in increased development and yield of the crop. Chakraborty et al [56] also concluded that LAI tended to increase with PAR interception due to the increment in canopy volume.…”
Section: Leaf Area Index (Lai)mentioning
confidence: 99%